A critical analysis of the Ugandan Companies Act, 2012, in the search for an appropriate legal framework for small and closely-held companies in the light of the experiences of South Africa and the United Kingdom - Engoru, Ivan (Department of Commercial Law, 2025)
This study set out to determine whether the Ugandan Companies Act, 2012 (‘CA 2012') provides an appropriate and effective legal framework for small and closely-held companies (‘SCHCs'). In this study, SCHCs are small owner-managed companies with one or a few members with close relations who are usually natural persons. The study focus follows from a recognition that companies' legislation in Uganda is complex and makes little attempt to provide simple, flexible and accessible law for the operations of SCHCs. Although this gap was highlighted during the enactment of CA 2012, it had also characterised previous companies' legislation in Uganda. The expectation was that CA 2012 would address this gap. However, there is doubt if this has been achieved. To be sure, what amounts to simple, flexible and accessible legislation for SCHCs is not obvious. However, a look at the relevant legislation in the comparable jurisdictions of South Africa and the United Kingdom suggests that SCHCs require special recognition and treatment in legislation in the areas of audits; financial reporting; limitation of membership; restriction of members to natural persons; and clear optional provisions. This can be achieved through a distinct corporate form in terms of a separate and distinct legislation for SCHCs or by treating SCHCs as private companies under a single company law statute, but with flexible provisions. In discharging this task, the study examines the various business forms under CA 2012 (ss 2, 4 and 5), and the corporate governance framework (ss 14, 138, 154, and 167). Through doctrinal analysis, it employs the evaluative framework of fewer reporting obligations; limiting membership in SCHCs to natural persons; limiting members who are also usually in management; and clear elective or optional provisions for SCHCs in areas such as company meetings and audits, as best practice on the regulation of SCHCs. The study draws on the experiences of South Africa under the Close Corporations Act 69 of 1984 (‘CCA 84') and South African Companies Act, 71 of 2008 (‘CA 2008'); and the UK's Companies Act, No. 46 of 2006 (‘CA 2006') as comparable jurisdictions; and the application of common law in companies' legislation. In the latter, I examine specifically the common law concept of quasi-partnership companies, and its' utility in the SCHCs category, and codification of common law in companies' legislation, as a growing drafting style. I draw some lessons from the UK and South Africa. The key arguments in this study are that first, the business forms and legal categories under CA 2012 do not align with the known legal definition or 2 characterisation of SCHCs. They are classified along the traditional lines of private versus public or unregistered versus registered companies. The single member company (‘SMC') is a new concept in Uganda's company law and is exclusive to single members. This does not cater for SCHCs. Second, the Code of Corporate Governance (‘CoCG') (s 14), although optional for private companies, contains complex concepts which are inapplicable to SCHCs. Thus, CoCG's significance to SCHCs' corporate governance needs is doubtful. Thirdly, the requirements for accounts reporting (s 154) and audit (s 167) are mandatory for all companies irrespective of their size or type. These provisions are elaborate with prescribed formats. Subjecting SCHCs to the same regulatory requirements as the other companies is burdensome and contrary to best practice. Finally, the comparable jurisdictions of the UK and South Africa have codified aspects of common law by way of a restatement of the law in their respective companies' legislation. A restatement serves two purposes. First, it directly integrates common law into statute; and second, affords the courts the flexibility to fill gaps that may exist in statute. This study contends that this tool (also loosely referred to as ‘codification') has not been well utilised in CA 2012 with respect to SCHCs. The study concludes that CA 2012 does not provide an appropriate and effective legal framework for SCHCs. Consequently, in keeping with best practice on the regulation of SCHCs as can be seen in comparable jurisdictions of South Africa and the UK, the study proposes amendments to ss 2, 4, 5, 138, 154, and 167 of CA 2012 to provide for the special regulation of SCHCs either (a) by creating a new type of company and rendering it subject to separate regulatory provisions or (b) to a ‘reduced' version of the regulatory provisions applicable to other companies; or by continuing to treat SCHCs as private companies and rendering them subject to a ‘reduced' version of the regulatory provisions applicable to other companies. To give effect to these proposals will require: (1) merging SMC with other smaller companies whose members do not exceed ten to create SCHCs founded on partnership principles; (2) inserting a chapter in CA 2012 with clear provisions which apply to SCHCs; (3) restricting membership of SCHCs to natural persons; and (4) inserting a general statement of purpose by way of a substantive provision in CA 2012 to the effect that in its interpretation the common law shall apply as a direct way of integrating the common law in CA 2012, as other jurisdictions have done. The study provides in Appendix B a Schedule of the proposed amendments and their justification to aid policy reforms and the review of CA 2012 with respect to SCHCs in Uganda.